VD_FINDINFO Pron / 2014 / 33 vom 24. März 2014 - VD Tribunal cantonal (2014)
AVOCAT, LOI FÉDÉRALE SUR LA LIBRE CIRCULATION DES AVOCATS, HONORAIRES, MODÉRATION | 45 al. 1 LPAv, 45 LPAv, 50 al. 1 LPAv, 50 al. 3 LPAv, 50 al. 4 LPAv, 50 LPAv